2022
DOI: 10.1128/spectrum.02348-21
|View full text |Cite
|
Sign up to set email alerts
|

No Effect of Lactobacillus rhamnosus GG on Eradication of Colonization by Vancomycin-Resistant Enterococcus faecium or Microbiome Diversity in Hospitalized Adult Patients

Abstract: Whereas other studies exploring the effect of L. rhamnosus in clearing VREfm from the intestine included children and adults, with a wider age range, our study consisted of a geriatric patient cohort. The natural clearance of VREfm in this study was almost 60% after 4 weeks, thus much higher than described previously.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(19 citation statements)
references
References 59 publications
0
2
0
Order By: Relevance
“…In a previous randomized clinical trial we found the VREfm carriers to be a homogeneous group with a high Charlson comorbidity index of 4. 5 The patients included in the study have only been retested on hospital readmission. Therefore, we cannot determine the time of decolonization based on these data.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a previous randomized clinical trial we found the VREfm carriers to be a homogeneous group with a high Charlson comorbidity index of 4. 5 The patients included in the study have only been retested on hospital readmission. Therefore, we cannot determine the time of decolonization based on these data.…”
Section: Discussionmentioning
confidence: 99%
“… 4 In a previous clinical trial, investigating the effect of probiotics on eradication of VREfm colonization in an elderly, comorbid and immunocompetent population, the number of participants with spontaneous decolonization was higher than expected: 56% after 4 weeks, and 90% after 24 weeks in the placebo group. 5 …”
Section: Introductionmentioning
confidence: 99%
“…In the study by Roghmann et al, they showed a natural VREfm clearance of only 33% over a three-year study period [24]. An RCT by our group found that almost 60% of patients in the placebo arm cleared VREfm after four weeks, thus constituting the spontaneous clearance [25].…”
Section: Introductionmentioning
confidence: 76%
“…Therefore, a total of six articles, published between 2007 and 2022, met the inclusion criteria and were included in this review. The trials were conducted in Australia [29], the United States [31,38], Denmark [25], Poland [30], and France [39]. An overview of the screening and inclusion of records can be found in Figure 1 adapted from the PRISMA statement [36].…”
Section: Study Design and Selectionmentioning
confidence: 99%
See 1 more Smart Citation